Обробка зображень з використанням суперпіксельної сегментації - Лавошник, І. О. (ХНУРЕ, 2025)
Superpixel segmentation enhances image processing by grouping pixels based on color, texture, and spatial features. This paper explores its role in nor-malization, classification, and object detection, improving efficiency and preserving key structures. Key methods, benefits, and integration with deep learning are discussed. Superpixel-based techniques help reduce computational complexity while maintaining essential image details. Future advancements may further optimize segmentation accuracy and adaptability in various applications.
Keywords: обробка зображень; суперпіксельна сегментація; суперпіксель